Implementasi Keaktifan Siswa dalam Pembelajaran IPS Berbasis Gender: Studi Analisis pada Siswa Kelas IX - Nuraeni, Intan; Himmatul Ulya (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
This study aims to analyze students’ levels of learning engagement by gender in social studies classes at SMPN 14 Semarang, as measured across the cognitive, affective, and psychomotor domains. The research method employed a descriptive qualitative approach, with the sampling technique focusing on students who played an active role during social studies lessons. Data collection was conducted through interviews, observations, and documentation. The research subjects were students in Class IX D. The results showed that female students were more dominant in actively participating in class across all three domains, with a percentage of 73.33% during Social Studies lessons, compared to male students at 20%. This was because female students had a better grasp of the Social Studies material due to their habit of preparing for class before lessons began, whereas male students lacked the motivation to prepare for Social Studies lessons beforehand, resulting in female students dominating classroom participation. Based on the research findings, it can be concluded that female students demonstrated higher levels of participation than male students in the cognitive, affective, and psychomotor domains during Social Studies lessons. This finding makes an important contribution by highlighting that student engagement based on gender still requires the implementation of more inclusive and interactive learning strategies. These strategies need to be designed to encourage balanced increases in student engagement, without favoring one gender over the other. Keywords: Gender-Based, Social Studies Learning, Student Engagement.